1994
DOI: 10.1002/em.2850240308
|View full text |Cite
|
Sign up to set email alerts
|

Etoposide (VP‐16) is a potent inducer of micronuclei in male rat meiosis: Spermatid micronucleus test and DNA flow cytometry after etoposide treatment

Abstract: The genotoxic and cytotoxic effects of etoposide (VP-16), a topoisomerase II inhibitor, on male rat spermatogenic cells were studied by analysing induction of micronuclei during meiosis. Micronuclei (MN) were scored in early spermatids after different time intervals corresponding to exposure of different stages of meiotic prophase. Etoposide had a strong effect on diplotene-diakinesis I cells harvested 1 day after exposure, and a significant effect also on late pachytene cells harvested 3 days after exposure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Unless sperm chromatin was adequately and timely exposed to ooplasmic topo II at the M phase, the torsional stress on DNA during chromatin remodeling would not be relieved completely, leading to strand breaks. This may explain why structural aberrations were significantly induced in paternal chromosomes when sperm nuclear development was delayed behind egg development in cross-fertilization 17 between Chinese hamster spermatozoa and Syrian hamster oocytes [42,43], and it may explain the significant increase of structural aberrations in paternal chromosomes of mouse embryos produced by delayed sperm injection into parthenogenetic eggs [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unless sperm chromatin was adequately and timely exposed to ooplasmic topo II at the M phase, the torsional stress on DNA during chromatin remodeling would not be relieved completely, leading to strand breaks. This may explain why structural aberrations were significantly induced in paternal chromosomes when sperm nuclear development was delayed behind egg development in cross-fertilization 17 between Chinese hamster spermatozoa and Syrian hamster oocytes [42,43], and it may explain the significant increase of structural aberrations in paternal chromosomes of mouse embryos produced by delayed sperm injection into parthenogenetic eggs [44].…”
Section: Discussionmentioning
confidence: 99%
“…ICRF-193 was also clastogenic and aneugenic to mouse secondary oocytes [12]. Etoposide's ability to induce structural chromosome aberrations and aneuploidy in male meiosis has been reported in mice [13−16] and rats [17]. Furthermore, merbarone has been shown to be aneugenic to mouse spermatocytes [16,18].…”
Section: Introductionmentioning
confidence: 96%
“…The topoisomerase-II inhibitor etoposide now fills this slot . While etoposide is also effective during diplotene, when it induces breaks near centromeres that result in micronucleated spermatids (La¨hdetie et al, 1994), its mutagenicity during a portion of pachytene is of particular interest because these are the stages during which events associated with recombination are taking place. Indeed, crossingover in the p-c segment of Chromosome 7 was found to be significantly decreased in offspring conceived 25-32 days after injection with etoposide (Russell et al, 2000a), corresponding to midand early pachytene, the same interval during which deletion mutations could be induced by this chemical.…”
Section: Effect Of Exposed Germ-cell Stage On Nature Of Mutationsmentioning
confidence: 99%
“…When this analysis was conducted on bone marrow erythrocytes of mice treated with MER, the frequencies of CREST-negative MN were increased dose-dependently, indicating only a clastogenic effect [Wang and Eastmond, 2002]. In rodent spermatocytes, VP-16 and MER (80 mg/ kg) induced meiotic MN in vitro and in vivo which were analyzed in the subsequent stage of early spermatids Laehdetie, 1996, 1997;Laehdetie et al, 1994;Sjoblom et al, 1994]. Further analyses of meiotic MN induced in vivo by VP-16 (10 and 20 mg/kg) with CREST-staining and with FISH using the minor probe revealed that 58.8 -74.4% were signal-positive, depending on the treated stage of meiosis Laedetie, 1996, 1997].…”
Section: Introductionmentioning
confidence: 99%